1979
DOI: 10.2307/1942488
|View full text |Cite
|
Sign up to set email alerts
|

Selective Pressures and Coevolution in a Kelp Canopy Community in Southern California

Abstract: The community of epiphytes on the giant kelp Macrocystis pyrifera, is simple, consisting primarily of the bryozoans Membranipora membranacea, Hippothoa hyalina, and Lichenopora buskiana; the serpulid polychaete Spirorbis spirillum; and the hydroids Obelia sp. and Campanulaia sp. Abundances of the organisms vary rapidly, by an order of magnitude or more in 2 wk. In spite of this short—term unpredictability, broad patterns of distribution are predictable. Membranipora, the competitive dominant, is abundant durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
2

Year Published

1986
1986
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 46 publications
8
110
2
Order By: Relevance
“…Feifarek (1987) described how an epibiotic sponge impeded starfish predation on a spiny oyster, Barkai & McQuaid (1988) found that whelks in shells overgrown by a bryozoan were resistant to lobster predation, and Gil-Turnes et al (1989) reported that bacteria growing on the surface of shrimp embryos chemically defended the embryos from pathogenic fungi. Bach (1980) mentioned how normally immune corn may be moderately attacked by cucumber herbivores when grown intermixed with cucumber, Threlkeld et al (1993) found that zooplankton may become more susceptible to predation when fouled, and epibiotic bryozoans have been shown to increase the attractiveness of kelp blades for grazing fishes (Bernstein & Jung, 1979) and echinoids (Ryland, 1976). In contrast, Prescott (1990) could not discover any effect of scallop epibionts on predation by seagulls or whelks.…”
Section: Discussionmentioning
confidence: 99%
“…Feifarek (1987) described how an epibiotic sponge impeded starfish predation on a spiny oyster, Barkai & McQuaid (1988) found that whelks in shells overgrown by a bryozoan were resistant to lobster predation, and Gil-Turnes et al (1989) reported that bacteria growing on the surface of shrimp embryos chemically defended the embryos from pathogenic fungi. Bach (1980) mentioned how normally immune corn may be moderately attacked by cucumber herbivores when grown intermixed with cucumber, Threlkeld et al (1993) found that zooplankton may become more susceptible to predation when fouled, and epibiotic bryozoans have been shown to increase the attractiveness of kelp blades for grazing fishes (Bernstein & Jung, 1979) and echinoids (Ryland, 1976). In contrast, Prescott (1990) could not discover any effect of scallop epibionts on predation by seagulls or whelks.…”
Section: Discussionmentioning
confidence: 99%
“…The density of larval settlement may vary due to flow reduction within the canopy (Bernstein & Jung 1979, Jackson 1986. Peterson 1986, Duggins et al 1990).…”
Section: Biological Consequences Of Flow Reduction Through Canopiesmentioning
confidence: 99%
“…Several studies have documented a largely negative effect of fouling organisms on their seaweed hosts. For example, fouling may increase the drag on the host and result in dislodgement from the substrata (Dixon et al 1981, D'Antonio 1985, decrease resource availability and growth (D'Antonio 1985, Brawley 1992, Hurd et al 2000, and damage host tissue by mechanical anchoring (Gonzalez & Goff 1989), by enhancing breakage (Dixon et al 1981, D'Antonio 1985 and by influencing the palatability of the host to herbivores (Bernstein & Jung 1979, Wahl & Hay 1995, Karez et al 2000.…”
Section: Introductionmentioning
confidence: 99%